Analysis of Commuter Increase in Jabodetabek Using Commuter Line - Ardiansyah, Bayu; Tohir, Muhammad (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2024)
In big cities like Jabodetabek, transportation plays an important role in daily life. According to PT KAI statistics, one of the most popular land transportation routes in this area for local residents is the KRL Commuter Line between 2022 and 2024. This study aims to determine the number of KRL Commuter Line users in Jabodetabek, explain the variables that influence the number of users, and provide recommendations to improve the comfort and facilities offered on the KRL Commuter Line, especially in Jabodetabek. The method used in this study is purposive sampling, by interviewing KRL Commuter Line users in Jabodetabek. Descriptive analysis was used to examine the data collected, the findings showed that more people are using the KRL Commuter Line in 2024. Employees who consider the KRL Commuter Line more efficient because of its regular departure schedule and students who consider it cheaper than other modes of transportation are some of the factors that influence this growth.